The Effectiveness of Problem Based Learning (PBL) on Student Problem Solving Ability in Courses Food Quality Analysis - Lina - Mufidah (Jurnal Socia Akademika, 2022)
This learning model expresses concretely by involving students to find solutions to problems. This model also provides an opportunity for students to find ideas explicitly, as well as ideas related to the ideas that students have. So that students are encouraged to differentiate and integrate ideas that students already have. The research objective was to determine the effectiveness of the PBL learning method on problem solving abilities in the food quality analysis course. The method used is quasi-experimental. The research design used by giving a pre-test and also a post-test on the sample. This research was conducted in the odd semester of 2022-2023 at the Culinary Arts Study Program. The population in this study were all students in semester III of the 2022-2023 Academic Year of the Culinary Arts Study Program who took the Applied Nutrition course. The research sample was 34 students. The sampling technique uses total sampling. Data collection techniques use tests as the main data. The test in question uses the results of the pre-test and post-test given after learning. The data analysis used is descriptive data analysis, analysis of assumptions testing, gain testing and hypothesis testing. The results showed that there were differences in problem solving abilities between before and after being given the problem based learning method.